2020
DOI: 10.1063/5.0021701
|View full text |Cite
|
Sign up to set email alerts
|

Scalable wafer-to-fiber transfer method for lab-on-fiber sensing

Abstract: We present an efficient and flexible method to realize micro- and nano-optical structures on the tip of optical fibers. We demonstrate this approach for a fiber-tip sensor consisting of a photonic crystal (PhC) structure in a semiconductor membrane on the cleaved facet of a telecom fiber. The PhC structure is fabricated on a wafer by lithography and etching and then transferred to the fiber facet by a simple mechanical pickup process through an opening in the substrate, without the need for adhesives or a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…For this work, PhC structures with a hexagonal lattice were patterned on a 250 nm thick InP membrane, which is separated from a InP substrate by a 300 nm thick sacrificial InGaAs layer, following the fabrication methods described in [ 20 ]. Briefly, the photonic crystal is patterned on the InP membrane by electron beam lithography (EBL) followed by inductively coupled plasma reactive ion etching (ICP-RIE), using a SiN layer as a hard mask.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this work, PhC structures with a hexagonal lattice were patterned on a 250 nm thick InP membrane, which is separated from a InP substrate by a 300 nm thick sacrificial InGaAs layer, following the fabrication methods described in [ 20 ]. Briefly, the photonic crystal is patterned on the InP membrane by electron beam lithography (EBL) followed by inductively coupled plasma reactive ion etching (ICP-RIE), using a SiN layer as a hard mask.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed sensor probe is based on photonic crystal (PhC) fiber-tip sensors. Each sensor is assembled with a simple and controllable method, where a 2D photonic crystal is fabricated on a wafer by standard semiconductor fabrication methods, and then it is mechanically transferred to the fiber end-face [ 20 ]. This transfer method only requires a movable stage and a microscope camera, and different to similar techniques, it does not need adhesives or additional materials to maintain the PhC attached to the fiber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] This occurs due to an increase in the hydrogen content in silicon oxynitrides similar to hydrogenated amorphous silicon (a-Si:H) and also leads to a decrease in the optical bandgap. [16] Due to the small size, lightweight, and strong antielectromagnetic interference ability of optical fibers, some approaches [17] to transfer the micro-and nano-optical structures to the optical fiber facets were demonstrated and successfully used in spectral sensing. [18] One report studied the direct deposition of BGs on asingle-mode fiber (SMF) using electron beam deposition technique, nevertheless, the study was demonstrated for the single application wavelength with the reflection values of 50-80% (3-7 dB respectively).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Most traditional optical devices use the difference of refractive index of materials to construct a certain spatial structure shape to change the wavefront state [2,3] and then realize the manipulation of the optical field. In contrast, the "Lab-on-Fiber" technology can accurately manipulate the wavefront phase, polarization state, and environmental parameters through the microstructure on the side, [4,5] fiber end, [6,7] or inner, [8,9] so it has the characteristics of small size, flexible structure, dispersion-flattened, low transmission loss, and good biocompatibility. Especially in recent years, with the rapid development of metasurface technology, [10] scientists have integrated metasurface on optical fiber.…”
Section: Introductionmentioning
confidence: 99%